2021
DOI: 10.1039/d0gc02969f
|View full text |Cite
|
Sign up to set email alerts
|

Catholyte-free electroreduction of CO2 for sustainable production of CO: concept, process development, techno-economic analysis, and CO2 reduction assessment

Abstract: Electrochemical CO2 reduction (ECO2R) is considered as one of economically viable means to convert CO2 into useful products, for achieving carbon neutrality in the future. Many studies have been conducted...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…In the two-step process, CO 2 is first converted to CO, which is further reduced in a subsequent step to C 2+ products. For this reason, in Table S3, we have compiled a list of ground-breaking studies on CO 2 reduction to CO. , The main goal of the two-step process is to minimize the loss of CO 2 due to (bi)­carbonate formation, which can only be achieved when the reaction is performed in acidic or neutral conditions. However, most of the studies were performed in alkaline conditions, but it is possible to obtain relatively high FEs for CO in slightly acidic or near-neutral conditions and in membrane electrode assembly (MEA) based cells. An alternative technology, based on a solid oxide electrochemical cell (SOEC), has been developed and commercialized by Haldor Topsoe to convert CO 2 to CO, which has a claimed energy requirement of 6–8 kWh/Nm 3 CO .…”
Section: State Of the Art Of Co2r And Cor To C2+ Productsmentioning
confidence: 99%
“…In the two-step process, CO 2 is first converted to CO, which is further reduced in a subsequent step to C 2+ products. For this reason, in Table S3, we have compiled a list of ground-breaking studies on CO 2 reduction to CO. , The main goal of the two-step process is to minimize the loss of CO 2 due to (bi)­carbonate formation, which can only be achieved when the reaction is performed in acidic or neutral conditions. However, most of the studies were performed in alkaline conditions, but it is possible to obtain relatively high FEs for CO in slightly acidic or near-neutral conditions and in membrane electrode assembly (MEA) based cells. An alternative technology, based on a solid oxide electrochemical cell (SOEC), has been developed and commercialized by Haldor Topsoe to convert CO 2 to CO, which has a claimed energy requirement of 6–8 kWh/Nm 3 CO .…”
Section: State Of the Art Of Co2r And Cor To C2+ Productsmentioning
confidence: 99%
“…Figure 3 provides a high-level mind map of the materials covered in this review and potential opportunities to optimize electrode wettability in CO2 electrolyzers. Here we do not discuss in detail the advances in understanding and developing anode and cathode catalysts, membranes, and electrolyzer structures because there are many comprehensive reviews on these topics available already [55][56][57][58][59][60] . Instead, we begin this review by discussing the desired wetting conditions of the GDL and CLs for CO2RR based on the current understanding of the primary CO2RR regions and recent achievement on CO2RR performance via wettability adjustment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many TEA analyses were carried out to find the threshold for profitability. [3][4][5][6][7][8][9][10] The results showed that the Faradaic efficiencies of the target products, the current density of the electrolyzer, and carbonate formation are vital to determining the cost of fuel and chemical production from the CO 2 RR. 11,12 The use of gas diffusion electrodes has greatly enhanced the current densities of CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%